Community-based organizations' development-oriented activities: Assessing participatory bottlenecks and measuring households' willingness using Arnstein's ladder of citizen participation - Olutayo Odunola; Oluwafemi Odunsi; Daniel Awodele; Benson Diriyai (Economic and Environmental Studies (E&ES), 2019)
This paper assesses participatory bottlenecks that households found in development-oriented activities of Community-Based Organizations (CBOs) in the periods 1985-1999 and 2000-2014. It also examines households' willingness to participate in future development activities. This is aimed at determining whether CBOs and their development-oriented activities would be sustainable. The study was conducted across three Senatorial Districts in Oyo State, Nigeria. Relevant information was obtained through questionnaires which were administered to 1,104 sampled households. Descriptive statistics were used to analyze the data collected. The major bottlenecks to pro-development participation in the two periods under examination concerned financial and economic resources, as households were faced with financial problems, wealth disparity and uncooperative attitude among community members to the source of projects financing. In reference to these bottlenecks, among others, there exist a significant number of people who are not willing to participate in future pro-development activities of CBOs. The study concludes that the sustainability of the organizations could be guaranteed if the households' perceived participatory bottlenecks to CBOs' development-oriented activities are attended to by the government and external stakeholders in order to enhance households' willingness to participate in future CBOs' development-oriented activities.
Keywords: R10; R11; 330; non-governmental organizations; public participation; sustainability; Senatorial Districts